(untitled) (Perspectivas em Ciência da Informação, 2023)
Bibliometric assessment is an intense research topic with multiple applications, from the evaluation of faculty productivity and the researcher’s career trajectory, to the analysis of emerging trends and themes in a research area. In this study we analyzed the brazilian researchers’ résumés of 36 professors from a computer science department. To accomplish that we used publication data extracted from Lattes Platform, an online repository of brazilian researchers’ résumés. Our goal was to evaluate the productivity of each professor, in terms of both quantity and quality, over a five years period, as well as, the co-authorship network produced. Additionally, we investigated if the productivity of the researcher is a good predictor for PQ scholarship as, according to CNPq (Brazilian National Council for Scientific and Technological Development), one of the criteria to grant this scholarship is the professor’s curriculum